Harmonization of Standard Insurance Clauses: A Consumer Protection and Fairness Perspective: Harmonisasi Klausula Baku Asuransi: Perspektif Perlindungan Konsumen dan Keadilan - Margareta Kristiani Hartono; Gunardi Lie (Academia Open, 2025)
General Background: Standardized insurance contracts containing boilerplate clauses dominate the industry due to efficiency demands. Specific Background: However, these clauses create structural inequalities in bargaining power and limit consumers’ ability to understand or negotiate policy terms. Knowledge Gap: Existing regulations, including the Consumer Protection Law, prohibit unfair terms yet remain insufficient to address ambiguities, exoneration clauses, and inconsistencies between legal norms and market practice. Aims: This study analyzes the legal implications of standard insurance clauses, their impact on contractual fairness, and the necessity of harmonized regulation to protect consumers. Results: Findings reveal that unilateral clause drafting perpetuates information asymmetry and facilitates claim denials, while oversight by regulators and dispute-resolution bodies remains fragmented. Novelty: The study proposes a responsive regulatory model that integrates preventive supervision by the Financial Services Authority, normative statutory safeguards, and corrective judicial interpretation—particularly through doctrines such as contra proferentem and reasonable expectations. Implications: Harmonizing essential clauses can balance contractual freedom with substantive fairness, strengthen consumer protection, and enhance transparency and trust in Indonesia’s insurance ecosystem. Highlights: Highlights how boilerplate insurance clauses create structural bargaining power imbalances and legal uncertainty for consumers. Identifies the gap between consumer protection norms and their implementation in regulating standard insurance policy terms. Proposes a responsive regulatory model combining OJK supervision, statutory safeguards, and judicial doctrines such as contra proferentem. Keywords: Boilerplate Clauses, Insurance Contracts, Consumer Protection, Contractual Fairness, Harmonization